Integrating Local Wisdom into Digital Governance: A Qualitative Study of A'Bulo Sibatang and Digital Collaboration Behavior among Civil Servants in Jeneponto Regency - Khaidir Syahrul; Annisa Paramaswary Aslam; Nurul Fadilah Aswar; Rahmat Riwayat Abadi (PT. Maju Malaqbi Makkarana, 2026)
Digital transformation has become a strategic priority for local governments in improving public service quality, transparency, and administrative efficiency. However, the success of digital governance depends not only on technological infrastructure but also on the ability of civil servants to collaborate effectively across organizational boundaries. This study aims to explore the role of A'Bulo Sibatang local wisdom in fostering Digital Collaboration Behavior among civil servants in Jeneponto Regency. A qualitative case study approach was employed using in-depth interviews, observations, and document analysis involving government officials, civil servants, cultural leaders, and academics selected through purposive sampling. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. The findings indicate that the values of solidarity, mutual support, collective responsibility, and integrity embedded in A'Bulo Sibatang serve as important social capital that encourages knowledge sharing, interdepartmental coordination, and collaborative problem-solving in digital work environments. These cultural values strengthen trust and cooperation among civil servants and contribute to more effective digital governance practices. The study concludes that integrating local wisdom into organizational culture can support sustainable digital transformation and enhance collaborative performance within local government institutions.